Mempercepat Perkecambahan Benih Asam Jawa (Tamarindus indica Linn) Menggunakan Metode Perendaman - Lince Romauli Panataria; Chichi J. Manalu; Efbertias Sitorus (Jurnal Penelitian Pertanian Terapan, 2022)
ABSTRACT Tamarind constitutes orthodox seed which is impermeable to water so that it is difficult to be penetrated by water in its imbibitions process. Consequently, the seeds have longer dormancy time so that special treatment is needed to accelerate its seed development. This research was done by soaking the seeds in the PGPR solution with the concentration and the soaking duration which are different from the purpose in order to accelerate the tamarind seed germination of the tamarind. The research used RAL (complete random sampling) consisted of soaking time (L) – L1: 2 hours, L2: 4 hours, L3: 6 hours, and PGPR concentration (P) which was Po; without PGPR concentration (control), P1: 10 ml/L of water, P2: 20 ml/L of water, and P3: 30 ml/L of water. The combination of treatment was 12 combinations, and each of them was repeated 3 times. The tamarind seeds were soaked according to the treatment, dried up, and germinated. The result of the research showed that germinating the seeds in 6 hours with PGPR concentration of 30 ml/L of water could accelerate the seeds until 4 days, 100% of sprouting power, 2.5% of vigor index, and 1% of germination rate. Keywords: Tamarind, PGPR, Seed Soaking